Surface Properties and Permeability to Calcium Chloride of Fagus sylvatica and Quercus petraea Leaves of Different Canopy Heights - Bahamonde, Héctor A.; Gil, Luis; Fernández, Victoria (Frontiers in Plant Science, 2018)
Plant surfaces have a major degree of chemical and physical variability also in relation to different environmental conditions, organs and state of development. The potential changes on plant surface properties in association with environmental variations have been little explored so far. Using two model tree species (i.e., Quercus petraea, sessile oak and Fagus sylvatica, beech) growing in ‛Montejo de la Sierra Forest’, we examined various traits of the abaxial and adaxial surface of leaves of both species collected at a height of approximately 15 m (top canopy), versus 3.5 to 5.5 m for beech and sessile oak, lower canopy leaves. Leaf surface ultra-structure was analysed by scanning and transmission electron microscopy, and the surface free energy and related parameter were estimated after measuring drops of 3 liquids with different degrees of polarity and apolarity. The permeability of the adaxial and abaxial surface of top and bottom canopy leaves to CaCl2 was estimated by depositing 2 drops of 3 to 4 µl per cm2 and comparing the concentration of Ca in leaf tissues 24 h after treatment, and also Ca and Cl concentrations in the washing liquid. Higher Ca concentrations were recorded after the application of CaCl2 drops on to the veins and adaxial blade of top canopy beech leaves, while no significant evidence for foliar Ca absorption was gained with sessile oak leaves. Surprisingly, high amounts of Cl were recovered after washing untreated, top canopy beach and sessile oak leaves with deionised water, a phenomenon which was not traced to occur on lower canopy leaves of both species. It is concluded that the surface of the two species analysed is heterogeneous in nature and may have areas favoring the absorption of water and solutes as observed for the veins of beech leaves.